2004
DOI: 10.1165/rcmb.2003-0251oc
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Prostasin Gene Structure, Promoter Analysis, and Restricted Expression in Lung and Kidney

Abstract: Human prostasin is a membrane-anchored serine peptidase hypothesized to regulate lung epithelial sodium transport. It belongs to a unique family of genes on chromosome 16p11.2/13.3. Here we describe genomic cloning, promoter analysis, and expression of prostasin's mouse ortholog. The 4.3-kb mouse prostasin gene (prss8) has a six-exon organization identical to human prostasin. Prss8 spans two signal tagged-sites localized to chromosome 7. Multiple mRNA transcripts arise from two consensus initiator elements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 51 publications
4
30
0
Order By: Relevance
“…Prostasin has been implicated by several groups of investigators, including our own, in regulation of Na ϩ transport in mammalian epithelia (3,8,19,26,29,30). These suspicions are based on prostasin's phylogenetic similarity to a channelactivating peptidase in frog kidney cells (26,28), coexistence of prostasin and ENaC in several types of epithelia (29), identification of serine peptidase inhibitor-sensitive Na ϩ transport pathways in mammalian airway (3) and kidney (18,19,29) epithelial cells, stimulation of Na ϩ transport when mammalian prostasins and ENaC are expressed together in frog oocytes (8,28), and stimulation of Na ϩ uptake by incubation of mouse kidney cells with soluble prostasin (19). In vivo support for a physiologically significant role in Na ϩ homeostasis comes from studies in rats, which become hypertensive and increase urinary Na ϩ excretion after exposure to adenoviral vectors expressing human prostasin (30).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Prostasin has been implicated by several groups of investigators, including our own, in regulation of Na ϩ transport in mammalian epithelia (3,8,19,26,29,30). These suspicions are based on prostasin's phylogenetic similarity to a channelactivating peptidase in frog kidney cells (26,28), coexistence of prostasin and ENaC in several types of epithelia (29), identification of serine peptidase inhibitor-sensitive Na ϩ transport pathways in mammalian airway (3) and kidney (18,19,29) epithelial cells, stimulation of Na ϩ transport when mammalian prostasins and ENaC are expressed together in frog oocytes (8,28), and stimulation of Na ϩ uptake by incubation of mouse kidney cells with soluble prostasin (19). In vivo support for a physiologically significant role in Na ϩ homeostasis comes from studies in rats, which become hypertensive and increase urinary Na ϩ excretion after exposure to adenoviral vectors expressing human prostasin (30).…”
Section: Discussionmentioning
confidence: 97%
“…Prostate cells can secrete and shed a fraction of prostasins as soluble enzymes with the rest remaining attached by a glycosylphosphatidylinositol anchor (6). Immunolocalization, mRNA blotting, and in situ hybridization studies led to recognition that prostasin is robustly expressed in additional human and mouse tissues, including kidney, lung, and airway (8,26,29,34). Significantly, prostasin shares several similarities with a membrane-anchored frog protein, channel-activating protease, identified by expression cloning as a regulator of Na ϩ transport in Xenopus kidney cells (24,25).…”
mentioning
confidence: 99%
“…Immunohistochemical studies revealed its presence in epithelial cells of the prostate gland, which inspired naming the enzyme prostasin. Subsequent studies revealed expression by epithelial cells of many organs (36,38). Sequencing of cDNA revealed a sequence predicting initial synthesis as a membrane-anchored, zymogen with an NH 2 -terminal prepro-segment and a COOH-terminal transmembrane peptide anchor (38).…”
mentioning
confidence: 99%
“…Expression cloning strategies identified a channel-activating protease (CAP) (34). Data-mining and phylogenetic analysis identified mammalian prostasin as a likely CAP ortholog (8,34,36) alternatively termed CAP1. Among several mammalian epithelial serine proteases with potential to activate ENaC, prostasin/CAP1 is a leading candidate as an endogenous regulator of Na ϩ transport, as reviewed in Ref.…”
mentioning
confidence: 99%
“…It was purifi ed as a soluble enzyme from human seminal fl uid and is highly expressed in kidney, lung, pancreas, and prostate in mice and humans ( 26,27 ). As a GPI-AP, PRSS8 can be removed from the cell membrane by treatment with PI-PLC ( 28 ).…”
Section: Prss8/prostasinmentioning
confidence: 99%